The plight of female entrepreneurs in India - Artee Aggrawal; Jon Carrick; Jeffrey Kennedy; Giovanni Fernandez (Economies, 2022)
Women from around the world are making substantive contributions to new ventures. Research on this phenomenon is starting to increase, but to this point, most of the research on female entrepreneurship has only examined it from the perspective of developed countries. As such, there is a gap in understanding this phenomenon from the perspective of developing countries. Due to the lack of theoretical underpinnings, and exploratory research approach to unearthing new ideas was called for. Using 10 female entrepreneurs as case studies and depth interviews as the main source of data, this study explores female entrepreneurship in India. The study's findings suggest that deep-rooted gender bias and family pressures are major challenges that female entrepreneurs in India face. This study's findings also suggest that supportive husbands, stress management, and maintaining a good work-life balance are important to helping female high-tech entrepreneurs in India overcome the challenges that they face. The results from this study inform the literature on the plight of female entrepreneurs in India, and more broadly, the study contributes to the understanding of the challenges that female entrepreneurs all around the world face.
Keywords: 330; female entrepreneurship; female high-tech entrepreneurs; high-tech entrepreneurship; women entrepreneurs; women entrepreneurship